Characteristics of head frequency response in blunt impacts: a biomechanical modeling study - Li, Guibing; Xu, Shengkang; Xiong, Tao; Li, Kui; Qiu, Jinlong (Frontiers in Bioengineering and Biotechnology, 2024)
Existing evaluation criteria for head impact injury are typically based on time-domain features, and less attention has been paid to head frequency response for head impact injury assessment. The purpose of the current study is therefore to understand the characteristics of human body head frequency response in blunt impacts via finite element (FE) modelling and wavelet packet analysis method. FE simulation results show that head frequency response in blunt impacts could be affected by the impact boundary condition, head energy peak and its frequency increase with the increase of impact, a stiffer impact block is associated with a higher head energy peak and a bigger impact block could result in a high proportion of the energy peak. Regression analysis indicates that only the head energy peak has high correlation with exiting head injury criteria, which implies that the amplitude-frequency aggregation characteristic but not the frequency itself of the head acceleration response has predictability for head impact injury in blunt impacts. The findings of the current study may provide additional criterion for head impact injury evaluation and new ideas for head impact injury protection.